2007
DOI: 10.1016/j.virol.2007.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the neutralization breadth of the anti-V3 antibody F425-B4e8 and re-assessment of its epitope fine specificity by scanning mutagenesis

Abstract: The identification of cross-neutralizing antibodies to HIV-1 is important for designing antigens aimed at eliciting similar antibodies upon immunization. The monoclonal antibody (mAb) F425-B4e8 had been suggested previously to bind an epitope at the base of V3 and shown to neutralize two primary HIV isolates. Here, we have assessed the neutralization breadth of mAb F425-B4e8 using a 40-member panel of primary HIV-1 and determined the epitope specificity of the mAb. The antibody was able to neutralize 8 clade B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
93
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(98 citation statements)
references
References 92 publications
(147 reference statements)
5
93
0
Order By: Relevance
“…Previously, we along with others have demonstrated that HIV-2 Env could be used as a scaffold to present HIV-1 MPER and CD4i epitopes in the context of a functional glycoprotein and that such viruses could serve as sensitive and specific probes for HIV-1-elicited epitope-specific NAbs (18,19,34,61,102 In the present study, we focused on HIV-1 V3, which continues to attract substantial attention as a target of NAbs (2,54,72,74,76,99,107). Mamounas and colleagues first demonstrated that a chimeric virus containing an HIV-2 backbone and an HIV-1 MN V3 loop was capable of infecting human T cells and showed susceptibility to HIV-1 V3-specific antiserum (64).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Previously, we along with others have demonstrated that HIV-2 Env could be used as a scaffold to present HIV-1 MPER and CD4i epitopes in the context of a functional glycoprotein and that such viruses could serve as sensitive and specific probes for HIV-1-elicited epitope-specific NAbs (18,19,34,61,102 In the present study, we focused on HIV-1 V3, which continues to attract substantial attention as a target of NAbs (2,54,72,74,76,99,107). Mamounas and colleagues first demonstrated that a chimeric virus containing an HIV-2 backbone and an HIV-1 MN V3 loop was capable of infecting human T cells and showed susceptibility to HIV-1 V3-specific antiserum (64).…”
Section: Discussionmentioning
confidence: 98%
“…We tested the ability of the HIV-2 KR.X7 /HIV-1 V3 chimeras to detect V3-specific antibodies using two HIV-1 MAbs, 447-52D and F425 B4e8, whose V3 epitope specificities are well established (2,72,93,108). HIV-2 KR.X7 YU2 V3 was potently neutralized by both 447-52D and F425 B4e8 (IC 50 s of 0.001 g/ml and 0.004 g/ml, respectively), and HIV-2 KR.X7 Ccon V3 was also effectively neutralized by the same antibodies but at higher concentrations (IC 50 s of 0.03 g/ml and 0.48 g/ml, respectively) ( Table 1 and Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The tip of the V3 loop is then able to dock with the cellular chemokine co-receptor (CXCR4 or CCR5), which ultimately leads to virus entry into the cell. Several crystal structures are now available for neutralizing antibody fragments bound to peptides derived from the HIV-1-gp120 V3 loop [166][167][168][169][170].…”
Section: Epitope Mimeticsmentioning
confidence: 99%